De-epithelialized Dermal Flap to Reduce Sacral Wound Healing Complications After Lower Body Lift Procedure. (25th January 2022) - Zaussinger, Maximilian; Wenny, Raphael; Schwartz, Bernhard; Ehebruster, Gudrun; Huemer, Georg M; Schmidt, Manfred
Abstract: Background: Lower or circumferential body lift procedures in the massive-weight-loss population have been associated with significant complication rates. Particularly, the sacral area is at risk of wound-healing problems due to high wound tension or shear forces. Objectives: The authors introduced a de-epithelialized dermal flap to reinforce the sacral area. Methods: Within this retrospective study, outcomes of 40 consecutive patients who underwent lower body lift between 2017 and 2021 were analyzed. The patient population was divided into 2 study groups (sacral flap vs no flap) including 20 patients each. Demographic and surgical data as well as complications were evaluated and compared. Appropriate statistical analysis was performed. Results: Thirty-seven female and 3 male patients with a median age of 36.5 years (range, 23-54 years) and a mean weight loss of 46.3 ± 12 kg participated in the study. The most common complication was sacral wound dehiscence (n = 7, 17.5%), and its occurrence was statistically significantly lower in the sacral flap group ( P = 0.037). The odd ratios for complications when executing the sacral flap procedure were reduced to 0.306 (95% confidence interval = 0.075 to 1.246) and 0.261 (95% confidence interval = 0.055 to 1.250) for the uncorrected and corrected logistic regressions, respectively. In addition, findings showed a significantly shorter hospital stay as well as statistical trends towards a lower occurrence of overall complications in the sacral flap group. Concerning the remaining data, no statistically significant differences between study groups were detected. Conclusions: The presented de-epithelialized dermal flap leads to a significant reduction of sacral wound-healing complications and a shorter hospital stay for patients. This surgical technique is easily reproduceable, rapid, and effective; therefore, we would recommend it for each circumferential or lower body lift procedure. Level of Evidence: 4: